Total Synthesis of the Diterpenoid (+)‐Harringtonolide. (16th August 2016) - Zhang, Hai‐Jun; Hu, Lin; Ma, Zhiqiang; Li, Ruining; Zhang, Zhen; Tao, Cheng; Cheng, Bin; Li, Yun; Wang, Huifei; Zhai, Hongbin
Abstract: Described herein is the first asymmetric total synthesis of (+)‐harringtonolide, a natural diterpenoid with an unusual tropone imbedded in a cagelike framework. The key transformations include an intramolecular Diels–Alder reaction and a rhodium‐complex‐catalyzed intramolecular [3+2] cycloaddition to install the tetracyclic core as well as a highly efficient tropone formation.